Analisis penetapan tarif kamar menggunakan metode activity based costing pada Merapi Merbabu Hotel Bekasi - Matheos, Militia; Alexander, Stanly W.; Kalalo, Meily Y. B. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Every hotel has the same goal, namely increasing sales of room services at a high percentage level. One way that management can take to achieve a high percentage level is by setting appropriate room prices. The purpose of this research is to find out the calculations for Merapi Merbabu Hotel Bekasi, whether in the process an appropriate calculation of the basic price of service products has been realized, and has taken into account the actual costs absorbed. The type of research used in this research is descriptive qualitative research. Data collection techniques use interviews, observation and documentation. The research results show that the overall calculation using the activity-based costing method for the basic price per room type is understate or below the basic price calculation carried out by the Merapi Merbabu hotel. Applying Activity Based Costing to determine room rates is more efficient because it can allocate various activity costs to each room type appropriately based on the consumption of each activity.